Faktor Risiko Siklus Menstruasi pada Remaja Putri di Kota Palangka Raya - Nila Susanti (FORIKES, 2021)
Nutritional status is one of the factors that influence the occurrence of menstrual cycle disorders affecting work in the form of increased, balanced or decreased hormones. Nutritional status potentially cause interference with the reproductive health of young women. Obesity that continues into adulthood will lead to earlier sexual maturity and irregularity in the menstrual cycle. While lack of nutrition for a student will result in a decrease in reproductive function. This research aims to analyze the effect of nutritional status and fat intake on the menstrual cycle of young women in Palangka Raya City. The design of this study was case-control with a ratio of 1:1. The case was young women with irregular menstrual cycles, while the comparison was young women who have regular menstrual cycles. The dependent variable was the menstrual cycle, while the independent variables were nutritional status and fat intake. Data analysis was performed by descriptive, bivariate (Chi-Square). One of the variables was a risk factor for irregular menstrual cycles, namely the nutritional status of adolescents (p = 0.035; OR = 2.228) but fat intake did not affect the menstrual cycle of young women. Nutritional status influenced the nutritional status of young women and nutritional intake did not risk factors for irregular menstrual cycles in young women. Keywords: menstrual cycle; young women; nutritional status; fat intake ABSTRAK Status gizi adalah salah satu faktor yang mempengaruhi terjadinya gangguan siklus haid mempengaruhi kerja berupa peningkatan, keseimbangan ataupun penurunan hormon. Status gizi memiliki potensi menimbulkan gangguan pada kesehatan reproduksi remaja wanita. Obesitas yang berlanjut sampai masa dewasa akan mengakibatkan maturitas seksual lebih awal dan ketidakteraturan siklus menstruasi. Sedangkan kekurangan nutrisi pada seorang siswi akan mengakibatkan penurunan fungsi reproduksi. Tujuan penelitian ini adalah untuk menganalisis pengaruh status gizi dan asupan lemak dengan siklus menstruasi remaja putri di Kota Palangka Raya. Rancangan penelitian ini adalah kasus-kontrol dengan perbandingan 1:1. Kasus adalah remaja putri dengan siklus menstruasi tidak teratur sedangkan pembanding adalah remaja putri yang mempunyai siklus menstruasi teratur. Variabel terikat adalah siklus menstruasi sedangkan variabel bebas yaitu status gizi dan asupan lemak. Analisis data dilakukan secara univariat, bivariat (Chi-Square). Salah satu variabel merupakan faktor risiko tidak teraturnya siklus menstruasi yaitu status gizi remaja (p=0,035;OR=2,228) namun asupan lemak tidak berpengaruh terhadap siklus menstruasi remaja putri. Status gizi berpengaruh terhadap status gizi remaja putri dan asupan lemak bukan faktor risiko tidak teraturnya siklus menstruasi pada remaja putri. Kata kunci: siklus menstruasi; status gizi; remaja putri; asupan lemak